Inactivation Kinetics of Pathogenic and Nonpathogenic Bacteria Upon In Vitro Treatment With Cold Atmospheric Pressure Plasma (CAPP) - Venetia Samioti; Evangelia Kriti; Aikaterini Spanou; Theofania Tsironi; Efstathios Z. Panagou (International Journal of Food Science)
In the present study, selected pathogenic (Salmonella Typhimurium, Escherichia coli, Pseudomonas aeruginosa, Listeria monocytogenes, Bacillus cereus, and Staphylococcus aureus) and nonpathogenic (Pseudomonas fragi, Pseudomonas fluorescens, Brochothrix thermosphacta, Bacillus subtilis, Lactiplantibacillus plantarum, and Leuconostoc mesenteroides) bacteria were subjected in vitro in cold atmospheric pressure plasma (CAPP) treatment for up to 15 min and the changes in the surviving microbial population were determined. Plasma treatments were carried out by a plasma jet device, operating with argon (Ar) as carrier gas under constant flow (4.0 L/min) at a frequency of 1 MHz and an electrical voltage of 2–6 kV. Microbial inactivation data were modelled using linear and nonlinear (Geeraerd, Weibull) models, through which the corresponding kinetic parameters were calculated. After 15 min of exposure to plasma radiation, the total reduction in the bacterial populations was 2.12 log10 CFU mL−1 for P. fragi, 1.77 log10 CFU mL−1 for P. fluorescens, 2.30 log10 CFU mL−1 for B. thermosphacta, 1.58 log10 CFU mL−1 for B. subtilis, 1.31 log10 CFU mL−1 for L. plantarum, 3.80 log10 CFU mL−1 for L. mesenteroides (highest reduction observed), 1.12 log10 CFU mL−1 for S. Typhimurium, 1.18 log10 CFU mL−1 for E. coli, 1.43 log10 CFU mL−1 for L. monocytogenes, 1.32 log10 CFU mL−1 for B. cereus, 0.88 log10 CFU mL−1 for S. aureus, and 0.73 log10 CFU mL−1 for P. aeruginosa. The results showed a higher reduction in the population of nonpathogenic microorganisms compared to pathogens. The relatively small decrease in the inactivation of bacteria indicates that parameter optimization is necessary to be considered to improve the efficacy of the treatment.